THE INFLUENCE OF HEART RATE VARIABILITY ON CLINICAL COURSE OF CHRONIC HEART FAILURE AND RENAL FUNCTION IN ATRIAL FIBRILLATION PATIENTS - E. A. Polyanskaya; S. V. Mironova; N. A. Koziolova (Российский кардиологический журнал)
Aim. Evaluation of structural and functional condition of the left ventricle (LV) and kidneys in permanent atrial fibrillation patients (AF) with ischemic chronic heart failure (CHF) according to mean 24 hour heart rate and heart rate variability.Material and methods. Sixty patients, age 35-60 y. o., with permanent AF of ischemic origin. All patients underwent echocardiography for the dysfunction verification: systolic function was assessed by ejection fraction of the left ventricle by Simpson, diastolic function was assessed via the velocity of transmitral currents and visualization of tissues of the mitral valve; Holter ECG monitoring was done, as volumetric sphygmopletysmography of peripheral arteries, assessment of kidney function by Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) by creatinine and cystatin C, evaluation of the status of collagen production by the tissue inhibitor of matrix metalloproteases type 1 (TIMP-1), measurement of NT-proBNP. In the first part of the study, patients were selected to 3 groups: by GFR <30 mL/min/1,73 m2, 30-60 mL/min/1,73 m2 and >60 mL/min/1,73 m2. In the second — by cystatin C levels below or higher than the referent.Results. There is negative moderate correlation of the heart rate >110 bpm and SDNN (r=-0,64, p=0,040) and <70 bpm and SDNN (r=0,50, p=0,042); direct moderate correlation of cystatin C and mean 24 hour heart rate >70 bpm (r=0,44, p=0,022); negative moderate correlation of GFR by CKD-EPIcys and mean daily heart rate >110 bpm (r=-0,55, p=0,030). Correlational analysis also showed that in permanent AF and ischemic CHF the mean 24 hour heart rate correlates strongly with E/e’ (r=0,53, р=0,011) and with NT-proBNP (r=0,57, р=0,002). Also the negative strong correlation found for SDNN with mean 24 hour heart rate (r=-0,59, p=0,001), with NT-proBNP (r=-0,65, p=0,002), with EF LV (r=-0,50, p=0,019), with the relation E/e’ (r=-0,61, p<0,001), with TIMP-1 (r=-0,53, p=0,048), moderate — with the LV myocardial mass index (r=-0,41, p=0,026) and cystatin С concentration (r=-0,38, p=0,036).Conclusion. In patients with permanent AF comorbid with CHF of ischemic origin the risk of sudden cardiac death, estimated by SDNN, is in U-shaped relation with mean 24 hour heart rate. More prominent decrease of HRV reflecting the increase of sudden death risk was found in a range of 24 hour heart rate >110 bpm. With the increase of mean 24 hour heart rate there was increase of CHF severity, progression of LV diastolic dysfunction and renal dysfunction. Low HRV in a range of mean daily heart rate >110 bpm was associated with adverse cardiac remodeling presenting with LVH, and of kidney remodeling. One of possible mechanisms of the target organs with HRV decline, by our data, might be transformation of collagenolysis towards collagenogenesis in intracellular matrix, according to the dynamics of TIMP-1.